Etos, Patos, Logos sebagai Elemen Dasar Retorika - Huri, Vivi Silvia (Prophetica : Scientific and Research Journal of Islamic Communication and Broadcasting, 2023)
This study aims to examine in depth the meaning and experience of communicators and audiences in internalizing and applying ethos, pathos, and logos as basic elements of rhetoric in public communication in Indonesia. Thematic data analysis showed that communicator credibility (ethos), emotional management (pathos), and logical argumentation (logos) complement each other in building persuasive and meaningful communication. The findings confirm the importance of balancing the three rhetorical elements for effective public communication and enrich the theoretical understanding and practice of strategic communication in Indonesia. Further research is recommended to explore the dynamics of rhetoric in digital and cross-cultural communication. Keywords : Rhetoric, Ethos, Pathos, Logos, Public communication.